Clinical Determinants and Services Model on Referral Decisions for Childbirth in Primary Midwifery Services - Roichatul Djannah (Jurnal Ners, 2026)
Referrals for delivery are a crucial component of maternal health care systems to prevent more severe maternal complications. In primary midwifery care, referral decisions are influenced not only by the mother's clinical condition but also by midwifery service factors. This study aims to analyze the clinical and service determinants of referral decisions for delivery in primary midwifery care. The study used an analytical observational design with a retrospective approach. Data were obtained from the delivery register, partograph, and Puskesmas referral book for 2024 with a population of 174 and a sample of 121 deliveries. Data analysis was performed using univariate and bivariate analysis using Fisher's Exact Test and limited determinant modeling. The results showed that delivery referrals occurred in 8.3% of cases. Severe obstetric complications and certain midwifery service factors played a major role in the decision to refer deliveries. This study confirms that delivery referrals are an outcome of the primary midwifery service system that is influenced by the interaction of clinical and service factors